Supply of hydrocarbon fuel biological stability - Бойченко, С.В.; Кучма, Н.М. (Proceedings of National Aviation University (archive), 2004)
The existing methods of increase of biological stability fuel on two groups are systematized: physico-mechanical and chemical. Increase of the international flights and the climatic conditions of Ukraine indicate to a urgency of a biological injury fuel for jet engines problem. Expediency of introduction biocyde additives after the technological process of manufacture of fuel before its using are accentuated.